2018
DOI: 10.1111/apa.14220
|View full text |Cite
|
Sign up to set email alerts
|

A case report and literature review of autism and attention deficit hyperactivity disorder in paediatric chronic pain

Abstract: The inclusion of behavioural assessment and screening for neurodevelopmental comorbidity may be essential in addressing complex paediatric chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Recently, Lipsker et al (11) described the case of a 6-years-old girl with severe chronic pain since very early age (headaches, joint and muscle pain), and comorbid ASD and attention deficit/hyperactivity disorder (ADHD). The authors also describe JH and fatigue in this patient, as well as antecedents of chronic pain in her relatives.…”
Section: Ehlers-danlos Syndromes (Eds) and Autismmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lipsker et al (11) described the case of a 6-years-old girl with severe chronic pain since very early age (headaches, joint and muscle pain), and comorbid ASD and attention deficit/hyperactivity disorder (ADHD). The authors also describe JH and fatigue in this patient, as well as antecedents of chronic pain in her relatives.…”
Section: Ehlers-danlos Syndromes (Eds) and Autismmentioning
confidence: 99%
“…Although the magnitude of the co-occurrence between chronic pain and neurodevelopmental disorders such as ASD remains unknown (11), some data suggest that chronic pain is frequent among the ASD population. Bursch et al (12) reported that more than 20% of pediatric patients in a pain clinic in US presented with ASD traits.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, existing research suggests that children with chronic pain conditions may be at risk of having an undetected neurodevelopmental disorder, and due to such comorbidity display more functional impairments 38 , 48 and respond less well to treatment. Thus, there is an urgent need to scientifically evaluate the co-occurrence of ASD, ADHD, and pediatric chronic pain, and potential relations to pain and demographic factors.…”
Section: Introductionmentioning
confidence: 97%
“…We read with interest the paper ‘A case report and literature review of autism and attention deficit hyperactivity disorder in paediatric chronic pain' by Wiwe Lipsker et al. in Acta Paediatrica and would like to add some further paediatric aspects. The authors discussed the importance of adopting a broad paediatric and neuropsychiatric perspective and screening for neurodevelopmental comorbidities in children with chronic pain without any identified cause.…”
mentioning
confidence: 99%
“…However, the case description provides another important medical aspect that may be of clinical relevance for the child′s chronic pain.…”
mentioning
confidence: 99%